Ecosystem effects of fishing & El Niño at the Galápagos Marine Reserve - Eddy, Tyler D. (PeerJ, 2019)
The Galápagos Archipelago is home to a diverse range of marine bioregions due to the confluence of several cold and warm water currents, resulting in some of the most productive tropical marine ecosystems in the world. These ecosystems are strongly influenced by El Niño events which can reduce primary production by an order of magnitude, dramatically reducing energy available throughout the food web. Fisheries are an important component of the local economy, although artisanal and illegal overfishing have dramatically reduced the productivity of invertebrate and finfish resources in recent decades, resulting in reductions in catches for local fishers. The regionally-endemic sailfin grouper (Myctereoperca olfax), locally known as bacalao, was once the most important fished species in the Galápagos, but is now listed as vulnerable by the IUCN due to its limited range and dramatic declines in catch over time. It is unknown how reduction of this predatory species has affected ecosystem structure and function. In the absence of stock assessments, we used an estimate of unfished bacalao biomass from fishers’ ecological knowledge along with unfished biomass estimates of other heavily exploited stocks—lobster (Panulirus penicillatus and P. gracilis) and sea cucumber (Isostichopus fuscus)—to create historical, unfished versions of existing modern day ecosystem models. We used the unfished and modern versions of the ecosystem models to test the ecosystem effects of bacalao exploitation at the Bolivar Channel, located in the cold, west upwelling bioregion of the archipelago during both El Niño and non El Niño years, and at Floreana Island, in the warmer, central bioregion. Fishers’ ecological knowledge indicates that at present, the biomass of bacalao is at least seven times lower than when unfished. This reduced bacalao biomass is linked with a greatly reduced ecosystem role compared to when unfished, and ecosystem role is further reduced in El Niño years. Allowing bacalao populations to rebuild to at least half of unfished biomass would partially restore their role within these ecosystems, while also resulting in greater fisheries catches. Comparing ecosystem impacts caused by fishing and El Niño, fishing has had a greater negative impact on bacalao ecosystem role than regular El Niño events.